Les races de poules - Bernard Denis (Revue d'ethnoécologie)
The author intends to give out a very general study. First of all, he indicates that hens are traditionally classified into European races and Asian races, and then mentions some important historic facts. In France, little can be found on the races of hens in the agronomic literature until the publication of Charles Jacque's fundamental work, Le poulailler, in 1858. The introduction of Asian races in Europe, which began in England, took a noteworthy importance: heavier and more productive than the native races, they were widely crossbred with the latter and new populations stood out from them. The variations, especially morphological, which are one of the means to classify races, are briefly presented. Finally, some races are taken as examples, such as the four "big" which prevail in the branch of industry but are used in crossbreedings: Leghorn, Rhode Island, Cornish, White Rock.